The Formalist vs Realist Constructs on Marriage Registration in Indonesia: A Study of the Perspectives of Kyai from Nahdlatul Ulama in Rembang - Rozak, Abdul; Akbar, Hasan (Al-Mazaahib: Jurnal Perbandingan Hukum, 2023)
Marriage registration plays an important role in safeguarding the rights of a marriage. However, it is often overlooked for various reasons. The validity of unregistered marriages has been a topic of debate until now. This research aims to answer the problems: 1) What is the social construction of the NU Rembang elite regarding marriage registration in the Islamic Law Compilation? and 2) What is the view of the NU Rembang elite regarding marriages that are not registered?. To answer these two problems, in this research the author chose to use qualitative research with Peter L. Berger's social construction theory approach. Data obtainded by in depth interview to the NU Rembang elite selected who were active and involved in legal matters from both structural and non-structural circles, totaling four people, including: KH. Chazim Mabrur, KH Syarofuddin Ismail Qoimaz, KH Chamid Mabrur, and KH Ahmad Sunarto. Research findings show that based on social construction theory, the NU Rembang elite is divided into two groups, namely formalists and realists. The thoughts of the NU Rembang elite regarding marriages that are not registered based on this typology are as follows: for the formalist group, marriages that are not registered are still valid. Meanwhile, for the realistic group, marriages that are not registered are invalid. The implication of this research is that it highlights the differences in views between two groups of NU Rembang elites regarding marriage registration in the Compilation of Islamic Law. However, it should be noted that the researched issues related to marriage registration are only a small part of the legal issues of marriage in Indonesia. Therefore, further research is needed to explore other untouched issues, which can then be developed by future researchers.[Pencatatan perkawinan berperan penting dalam menjaga hak-hak dalam sebuah perkawinan. Akan tetapi, perkara ini sering kali diabaikan karena berbagai sebab. Keabsahan perkawinan yang tidak dicatatkan telah menjadi tema perdebatan hingga kini. Penelitian ini bertujuan untuk menjawab permasalahan: 1) Bagaimana konstruksi sosial elit NU Rembang tentang pencatatan perkawinan dalam Kompilasi Hukum Islam? dan 2) Bagaimana pandangan elit NU Rembang tentang perkawinan yang tidak dicatatkan? Untuk menjawab kedua permasalahan tersebut, dalam penelitian ini penulis memilih menggunakan penelitian kualitatif dengan pendekatan teori konstruksi sosial Peter L. Berger. Data diperoleh melalui interview mendalam kepada Elit NU Rembang yang aktif dan terlibat dalam masalah hukum baik dari kalangan struktural maupun non struktural yang berjumlah empat orang, antara lain: KH. Chazim Mabrur, KH Syarofuddin Ismail Qoimaz, KH Chamid Mabrur, dan KH Ahmad Sunarto. Temuan penelitian menunjukkan bahwa berdasarkan teori konstruksi sosial, elit NU Rembang terbagi menjadi dua kelompok, yaitu formalis dan realis. Pemikiran elit NU Rembang tentang pernikahan yang tidak dicatatkan berdasarkan tipologi tersebut adalah sebagai berikut: bagi kelompok formalis, pernikahan yang tidak dicatatkan tetap sah. Sedangkan bagi kelompok realis, pernikahan yang tidak dicatatkan adalah tidak sah. Implikasi dari penelitian ini adalah menyoroti perbedaan pandangan antara dua kelompok elit NU Rembang terkait registrasi pernikahan dalam Kompilasi Hukum Islam. Namun, perlu dicatat bahwa permasalahan yang diteliti terkait registrasi pernikahan hanya merupakan sebagian kecil dari permasalahan hukum pernikahan di Indonesia. Oleh karena itu, penelitian lebih lanjut diperlukan untuk mengeksplorasi isu-isu lain yang belum tersentuh, yang kemudian dapat dikembangkan oleh peneliti di masa depan.]